Design and analysis of magnetorheological fluid brake based on orthogonal test methods - YANG Guangxin; WANG Fei; ZHOU Long; WANG Daoming (Jixie chuandong)
ObjectiveIn order to optimize the structure of magnetorheological fluid (MRF) brake (MRB) for electric vehicles, the braking characteristics of the MRB were investigated through simulation analysis and experimental verification.MethodsBased on the analysis of the influencing factors of braking performance, 3 influencing factors of brake gap size, the quantity and the outer radius of the brake disks, and 3 evaluation indexes of viscous braking torque, normal braking torque, and maximum braking torque were selected for the orthogonal test.ResultsThe results show that the viscous braking torque is predominantly influenced by the brake gap size in the absence of magnetic field. However, after applying a magnetic field, the quantity of brake disks becomes the primary factor affecting the braking performance of the MRB, with the outer radius of the disks being the secondary factor. Under the same conditions, the viscous braking torque exhibits a negligible influence, in the case of h3n4R22, for example, the normal braking torque is about 68 times higher than the viscous braking torque. So the output braking torque can be adjusted within the controllable range by changing the magnetic field strength.